Pengaruh Metode Pembelajaran Picture And Picture untuk Meningkatkan Keaktifan Belajar Siswa Pada Pembelajaran Tematik Kelas III SD Negeri 0507 Pasar Latong - Nurhalimah Harahap; Era Mutiah (Journal Innovation In Education, 2023)
The aim of this research is to determine the effect of the picture and picture learning method to increase student learning activity in thematic learning. The research method used is an experimental research method, based on this type of research data in the form of quantitative research. The data collection techniques used by researchers are tests (pretest and posttest), observation and documentation. The population of this study was taken from class III at SD Negeri 0507 Pasar Latong and the sample in this study was taken from all 33 class III students. From the results of the "t" test, namely Tcount > Ttable, Ho is rejected and Ha is accepted.Based on the calculation results, it shows that the posttest average > pretest average, namely: 63.5 > 85.75. The results of hypothesis testing using the t test show that the value of T = 4.018, with a level of α = 0.05 with degrees of freedom (df) 33-1 = 32, the results obtained are T table = 1.697. The calculation results obtained Tcount > Ttable or 4.018 > 1.697, in accordance with the basic provisions for decision making that Ha is accepted and Ho is rejected, meaning that there is a significant influence of the picture and picture Learning method to increase students' active learning in class III thematic learning at SD Negeri 0507 Pasar Latong.